Quality management in heavy duty manufacturing industry: TQM vs. Six Sigma. (2nd January 2016) - Sabet, Ehsan; Adams, Elisabeth; Yazdani, Baback
Abstract : 'Is TQM a management fad?' This question has been extensively documented in the quality management literature, and is tackled in this research through a critical literature review on the area. The 'TQM vs. Six Sigma' debate, which has also been a fundamental challenge in this research field, is addressed by a thematic and chronological review of the peer papers. To evaluate this challenge in practice, a primary research in heavy duty machinery production industry has been conducted using a case-study on J C Bamford Excavators Ltd, the largest European construction machinery producer. The result highlights the fact that TQM is a natural foundation upon which to build Six Sigma; and not surprisingly the quality yield in a TQM approach complemented by Six Sigma is far higher and more stable than when TQM with no Six-Sigma focus is put in place, thus presenting the overall finding that TQM and Six Sigma are complements, not substitutes. The study concludes with an overview on quality management approaches in the heavy duty manufacturing industry to highlight the way forward.